SAFETY SYSTEM FOR LOCAL AREA NETWORK SYSTEM USING NETWORK OPERATIONS NOVELL NETWARE V3.12 ON GLOBAL SOLUSINDO COMPUTER - Erwin Erwin; Eko Hadiyanto, SSi, MM Eko Hadiyanto, SSi, MM (Jurnal Sistem Informasi, 2001)
With a network security system implemented at Global Solusindo Computer, the security of files and data stored on the server more secure from the ravages of use by the user, besides other positive impacts that supports teaching and learning activities so that the user poses a bias network using time available in an effective and efficient.Use a file or data contained on the server depending on the rights granted by the supervisor to the user. By granting rights to the directories related applications provided with teaching materials other than the security aspects of the user data and files in a server network.